Toughining of Epoxy-Resins Using Thermoplastic Materials as Modifiers - T. A. Himdan (Ibn Al-Haitham Journal for Pure and Applied Sciences, 2019)
Epoxy resins were modified using thermoplastics, such as polystyrene and poly (methylmethacrylate) (PMMA) or their monomers polymerized in situe. The modifications showed good results specially when (PMMA) was used. Thermal analysis of the modified polymers were studied using (DSC) and other physico-mechanical properties measurement.